Kemampuan Berpikir Kritis Dan Penguasaan Konsep Siswa Kelas V Melalui Pembelajaran Berbasis Proyek Berbantuan Zoom Meeting Pada Materi Perubahan Benda - Nurallam, Lestari; Nur Aeni, Ani; Sujana, Atep (Jurnal Pena Ilmiah, 2021)
Critical thinking skills are important to develop so that students are skilled in solving existing problems and so is the ability to master conceptsÂ  to the knowledge they have learned. In developing these abilities PjBL can be used as an alternative. The purpose of the study was to determine the critical thinking skills and concept mastery of fifth grade students through PjBL on zoom meetings the material of changing objects. The research method, namely descriptive qualitative. Data collection techniques used are observation and test questions. The results of this study include, the implementation of PjBL and ost of the students' critical abilities and mastery of concepts on zoom meeting on the material for changing objects for class V students in the very good category. So it can be concluded that PjBL on zoom meetings has a good impact on students' critical thinking skills and mastery of concepts.